Factors Determining Investor Acceptance Towards Islamic Finance in India - Mohammad Irfan; Shah Saeed Hassan Chowdhury; Sylva Alif Rusmita (Economica: Jurnal Ekonomi Islam, 2021)
Despite India, having the second largest Muslim population in the world, Islamic finance is in its nascent stage. It is important from the perspective of investor to understand the concept of Islamic Finance. The aim of this study is focused on factors affecting the acceptance of Islamic Finance in India. This study concentrated on the primary data collected from 354 investors from cities across India, using structured questionnaire through snowball sampling technique. Demographic profiles of respondents were compiled by using descriptive statistics. The factor analysis was done by using SPSS. Findings of the study reveal that the high degree of reliability and validity of the data as reflected by Crobach’s Alfa (α) at 0.86. Kaiser-Mayer- Olkin Measure of Sampling Adequacy (KMO) is .776, which is statistically significant. Factor analysis extracted highly loaded (Eigen value 1) six factors using 29 items in a structured questionnaire. Together these six factors explained total variance of 76.24%. These factors are namely viz., Awareness of Shariah indices, Religious motive, Social responsiveness, Understanding of Shariah screening, Ethical investment and Socio-economic reasons. Therefore, Islamic Finance and Shariah investment product planner should consider such factors seriously in designing their product marketing strategies.